Effect of Alcoholic Extract of Pomegranate Peel on Kidney Enzyme Levels, Histological Changes, in Male Albino Rats Treated with Methotrexate - Al-Jubori, Duaa A. H.; Ismael, Maha Hameed; Al-Shujairi, Marwa Najim Obied (American Journal of Biology and Natural Sciences, 2026)
Methotrexate (MTX) is highly nephrotoxic and acts via oxidative stress and inflammatory cascades. Pomegranate peel extract (PPE) contains punicalagins and exhibits potent antioxidant activity which is beneficial to the kidney. To assess the protective effects of pomegranate peel Extract (PPE) against methotrexate (MTX) induced renal damage in rats. Male Wistar rats were given PPE (400 mg/kg) for 10 days including one MTX injection (20 mg/kg) on day 7. Renal histology and serum biomarkers were, in turn, examined. following MTX administration, there was a marked increase in levels of blood urea (155% of baseline controls; 96.09±1.80 mg/dL) and blood creatinine (185% of baseline controls; 1.94±0.08 mg/dL; p<0.001). In MTX-treated kidneys, histopathological examination showed severe acute tubular necrosis, glomerular congestion and inflammatory cells infiltration. However, urea and creatinine levels in PPE pre-treatment group were significantly decreased to 54.24±1.76 mg/dL and 1.02±0.03 mg/dL respectively (p<0.01) thus these pathological alterations. In this study, the intervention resulted in a 43-47% decrease in nitrogenous waste products and significantly reduced renal architecture changes, which included absence of tubular dilations and preserved brush borders. The quantitative data demonstrates PPE ability to reverse the biochemical and structural changes caused by MTX, thereby demonstrating effective restoration of the renal filtration barrier and tubular secretory function. PPE is a potent nephro-protective agent that restores the renal markers and maintains the integrity of the renal tissues. It is an effective adjunctive therapy in clinical situations for reducing the side effects of chemotherapy.